Reconsidering copyright protection for software and databases. - Koutouki, Dina. (University of Ottawa (Canada), 1999)
Software and databases are tools utilized daily by a large variety of people. Copyright, in conjunction with other legal mechanisms and technological protection methods provides too much protection for these functional works. This is alarming since software and databases are generally the tools used to access and utilize information in today's society. Overprotection in these areas may lead to the creation of information monopolies, stifling innovation and putting at risk user rights. This is especially worrisome for information and information technology importing countries such as Canada. It is suggested that regardless of the type of protection afforded to software and databases the paramount interest needs to be society's ability to access information. This can be accomplished by limiting the scope of protection afforded to software and databases and expanding the fair dealing provisions in the Copyright Act. The end result being, increased rights for users, as well as, increased rights for inventors to built upon existing technology and knowledge.
Keywords: Law.